PENGUKURAN KINERJA PERUSAHAAN DAN SISTEM MANAJEMEN STRATEGIS - Yoyon Safrianto (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
Abstract Nowadays, the companies are in the middle of the information competition century.  To  achieve  competitive  success,  the  century  information  environment requires the new ability of the companies must be owned by the manufacturing and services. A company's ability to process information from a variety of instruments is absolutely need, steer the company to across the complex competitive environment. Company requires instrument which capable of explaining various aspects of the environment and performance in monitoring of travel towards a promising future. Balanced Scorecard provides an instrument that is required to steer the company toward the future success of the competition. An accurate understanding about the goals  and  methods  for  achieving  it  is  very  vital.  Balanced  Scorecard  translates mission and strategy of the company in to a comprehensive measure that provides a framework for measurement and strategic management system. Scorecard measures the performance of companies on the four perspectives of balanced: financial, customer. internal business processes, and learning growth. Balanced Scorecard enables companies to record financial performance results as well as monitor progress  in  building  the  company's  ability  and  to  obtain  intangible  assets  that required for future growth. Keywords: balanced scorecard, performance, and trategic management system